Harnessing Cannabis: Pain Management Strategies for Oncology Patients – A Narrative Review - Kopczyński, Cezary; Kopczyńska, Urszula; Malinowski, Piotr; Sikorski, Piotr; Gurdak, Kinga; Dydyk, Martyna; Dyrek, Martyna; Błaszczak, Ewa; Wójcik, Jakub; Partyka, Aleksandra (Journal of Education, Health and Sport, 2024)
Cancer-related pain represents a serious challenge in oncological care, often refractory to conventional analgesics and significantly impacting patients' quality of life. In recent years, medical marijuana (cannabis) has emerged as a potential adjunctive or alternative therapy for managing pain in oncological patients. This narrative review critically evaluates the existing literature on the efficacy, safety, and underlying mechanisms of action of medical marijuana in alleviating pain associated with cancer. Drawing upon a synthesis of preclinical and clinical studies, as well as meta-analyses and systematic reviews, this review provides insights into the scientific basis and clinical implications of utilizing medical marijuana in oncological pain management.